Efforts to Improve MSME Commodity Marketing in Tasikmalaya Regency during the Covid-19 Pandemic through Training and Mentoring Programs - Mohamad Arief Setiawan; Kalfin Kalfin; Perdi Setiawan (Research Collaboration Community (RCC), 2021)
The COVID-19 pandemic has had a very bad impact and decreased income in the Micro, Small, and Medium Enterprises (MSME) sector. An effort is needed that can increase the marketing of MSME products that are in accordance with consumer conditions. There are still many MSME actors who market their products in stores and in the market which are not in accordance with the conditions in the field. Continuous training and assistance are needed in introducing a marketing system that is in accordance with the conditions of the times. One of them is marketing using online media. Based on these circumstances, this study aims to determine efforts to increase the marketing of MSME commodities in Tasikmalaya Regency during the Covid-19 pandemic through training and mentoring programs. The method used in this research is descriptive quantitative. The data used were obtained from interviews with the help of a questionnaire given to MSME actors. Based on the results obtained, the use of online media in marketing MSME products was 19%. From the results of the analysis, it is found that the level of ability to use digital technology is 26%, which means that there are still many MSME actors who do not understand using digital technology, especially in creating online stores. Therefore, continuous training and assistance are needed in improving the understanding of MSME actors and keeping up with the times.